Anhedonia and suicidal ideation in young people with early psychosis: Further findings from the 2-year follow-up of the ReARMS program. (May 2023) - Poletti, Michele; Pelizza, Lorenzo; Loas, Gwenole; Azzali, Silvia; Paterlini, Federica; Garlassi, Sara; Scazza, Ilaria; Chiri, Luigi Rocco; Pupo, Simona; Raballo, Andrea
Highlights: Anhedonia is psychopathologically relevant in early psychosis. Anhedonia is crucial in predicting suicidal ideation (independent of depression). Anhedonia is relevant in preventing suicide over a prolonged illness course. Specific interventions on anhedonia may reduce suicide risk overtime. Abstract: Hedonic deficits have been extensively studied in schizophrenia, but little is known about their association with suicidal ideation in early psychosis. The aim of this research was to examine the relationship between anhedonia and suicidal thoughts across a 2-year follow-up period in people with First Episode Psychosis (FEP) and at Ultra High Risk (UHR) of psychosis. Ninty-six UHR and 146 FEP, aged 13–35 years, completed the Comprehensive Assessment of At-Risk Mental States (CAARMS) and the Beck Depression Inventory-II (BDI-II). The BDI-II "Anhedonia" subscale score to assess anhedonia and the CAARMS "Depression" item 7.2 subscore to measure depression were used across the 2 years of follow-up. Hierarchical regression analyses were performed. No difference in anhedonia scores between FEP and UHR individuals was found. In the FEP group, a significant enduring association between anhedonia and suicidal ideation was found at baseline and across the follow-up, independent of clinical depression. In the UHR subgroup, the enduring relationship between anhedonia and suicidal thoughts were not completely independent from depression severity. Anhedonia is relevant in predicting suicidal ideation in early psychosis. Specific pharmacological and/or psychosocial interventions on anhedonia within specialized EIP program could reduce suicide risk overtime.